The Prevalence of Amoebiasis in Children Admitted to Gastro Department at Children’s Hospital of Benghazi. - A. Abdusalam, Abdusalam; F. Alawaaj , Abdulsalam; H. Almabrouk , Zahoor (Benghazi University Medical Journal, 2025)
Abstract Background: Amoebiasis, caused by the protozoan parasite Entamoeba histolytica, remains a major public health concern, particularly in less developed and developing regions where sanitation standards are inadequate. Aim: To investigate the role of E. histolytica as a primary cause of gastroenteritis and to assess infection rates among children admitted to the Gastroenteritis Department at Benghazi Children’s Hospital over a one-year period. Method: A cross-sectional study was conducted by using records from the Parasitology Department between January and December 2023. A total of 1,443 stool samples were examined microscopically and categorized into four age groups: 1–3, 4–6, 7–9, and 10–14 years. Results: The overall prevalence of E. histolytica/dispar was 35.3%. Giardia lamblia infections accounted for 2.8%, while other microbial infections—including fungal organisms such as Candida spp.—represented 1.2%. The highest infection rate was recorded in the Gastroenteritis Department (59.0%), compared to 30.1% in the Outpatient Department. Seasonal trends showed a peak prevalence of 5.5% in August and the lowest rate of 1.3% in April. Conclusion: The study highlights the substantial burden of E. histolytica infections among children in Benghazi, emphasizing the urgent need for improved sanitation, enhanced public health strategies, and continuous monitoring to reduce infection rates.